PHYSICIAN ASSISTED SUICIDE: A NEW LOOK AT THE ARGUMENTS - Dieterle, J. M. (Bioethics, 2007)
In this paper, I examine the arguments against physician assisted suicide (PAS). Many of these arguments are consequentialist. Consequentialist arguments rely on empirical claims about the future and thus their strength depends on how likely it is that the predictions will be realized. I discuss these predictions against the backdrop of Oregon's Death with Dignity Act and the practice of PAS in the Netherlands. I then turn to a specific consequentialist argument against PAS – Susan M. Wolf's feminist critique of the practice. Finally, I examine the two most prominent deontological arguments against PAS. Ultimately, I conclude that no anti-PAS argument has merit. Although I do not provide positive arguments for PAS, if none of the arguments against it are strong, we have no reason not to legalize it.